1994
DOI: 10.1007/s002040050143
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localisation of six glutathione S-transferases within the nasal cavity of the rat

Abstract: Many xenobiotics induce lesions within the nasal cavity of experimental animals which are site specific. This site selectivity may be due to regional deposition within the nasal cavity and/or the localisation of biotransformation enzymes. We have developed methodology which allows immunohistochemical localisation of xenobiotic biotransformation enzymes in transverse sections of the rat nasal cavity identical to those normally taken for pathological examination. We report the application of this methodology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Protein pellets were solubilised in 0.1 ml 10% sodium dodecyl sulphate (SDS) and stored at )20°C. Whole heads were prepared for immunohistochemical examination as described previously (Banger et al 1994). After decalcification, heads were sectioned transversely into the four levels described by Young (1981) and were embedded in wax.…”
Section: Preparation and Treatment Of Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein pellets were solubilised in 0.1 ml 10% sodium dodecyl sulphate (SDS) and stored at )20°C. Whole heads were prepared for immunohistochemical examination as described previously (Banger et al 1994). After decalcification, heads were sectioned transversely into the four levels described by Young (1981) and were embedded in wax.…”
Section: Preparation and Treatment Of Tissuesmentioning
confidence: 99%
“…HSP70 was detected as described previously (Banger et al 1994) using primary and secondary antibodies diluted 1/1000 and 1/200, respectively, in 0.05 M Tris-HCl, pH 7.4. Sections were counterstained in Harris haemalum, dehydrated in graded alcohols, cleared in xylene and mounted in DPX mountant.…”
Section: Immunological Techniquesmentioning
confidence: 99%
“…Previous studies have shown high expression of GST protein and/or mRNA in the olfactory epithelium of rats (Banger et al 1993;Ben-Arie et al 1993). Immunoreactivities of GST were localized in the sustentacular cells and Bowman's gland of the olfactory epithelium in adult rats (Banger et al 1994) and rats during development (Krishna et al 1994). Our previous study reported that anosmia-induced rats (by zinc deficiency) showed decreased GST expression in the olfactory epithelium (Kudo et al 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Gene and protein expressions of MRP1 were preferentially localized in the supporting cells of the olfactory epithelia by both hisotochemical techniques. However, mammalian phase II enzymes, including glutathione S-transeferase (GST), were expressed in the supporting cells of olfactory epithelia [e.g., 3,18]. Our previous study demonstrated, zinc-deficient rats that exhibited olfactory dysfunction, a marked reduced expression of GST class mu at both mRNA and protein levels in supporting cells of olfactory epithelia [13].…”
mentioning
confidence: 99%